A phosphorus-containing imidazole derivative towards the liquid oxygen compatibility and toughness of epoxy resin. Issue 12 (1st March 2022) - Wang, Huihuan; Li, Chuan; Hou, Zhuang; Li, Bolun; Cai, Haopeng
Abstract : Thermosets modified with a P-containing imidazole derivative (VAD) exhibited simultaneous liquid oxygen compatibility and excellent mechanical properties. Abstract : In order to develop a liquid oxygen-compatible (LOX-compatible) matrix resins for polymer-based fiber-reinforced composites, a novel phosphorus-containing imidazole derivative called VAD containing multifunctional groups was synthesized and used as a co-curing agent for epoxy resin (EP) with simultaneous LOX-compatibility and mechanical improvement. A phosphorus group was introduced into the EP to capture the free radicals generated during the pyrolysis of the polymer to improve LOX compatibility, and the trimethylene group was introduced as a flexible spacer to enhance the toughness of the cured material. In comparison to pure EP, the modified EP with only 2.5 wt% VAD showed excellent mechanical properties with 23.0% and 75.6% increase in tensile and impact strength, respectively. Furthermore, as the content of VAD increased, a thermoset compatible with LOX (according to the liquid oxygen impact test) was obtained, and the flame retardancy was improved (according to the limiting oxygen index test). However, there was no significant sacrifice of transparency or thermal stability. In addition, the LOX compatibility mechanism was analyzed using X-ray photoelectron spectroscopy. As an efficient multi-functional modifier, VAD has a bright future in the modification realm of EP materials.